The effects of dust and heat on photovoltaic modules : impacts and solutions / Amir Al-Ahmed, Inamuddin, Fahad A. Al-Sulaiman, Firoz Khan, editors. - Al-Ahmed, Amir; Inamuddin, 1980-; Al-Sulaiman, Fahad A.; Khan, Firoz (Green energy and technology., 2022)
This resource begins by discussing the properties of dust accumulation on PV modules, and then presents several solutions, such as hydrophobic coatings and surface texturing. The second half of the book is used to discuss the effects of heat on silicon PV modules, as well as various cooling approaches. These include water cooling and carbon-based materials. Due to the prevalence of PV systems in renewable energy, this book will be of interest to numerous students, researchers and practitioners.